INFLUENCE OF NITROGEN ON THE TRANSPIRATION INTENSITY AND PRODUCTIVITY OF THE BUCKWEAT IN THE ZARAFSHAN VALLEY - Urokov, Sirojiddin (International Journal of Psychosocial Rehabilitation, 2020)
This article provides information on the effects of nitrogen norms on the intensity and productivity of transplants during the development phases of bark varieties grown in Zarafshan Valley as a secondary crop. It shows that the transpiration rate in the bark varieties grown in the Samarkand region as a second crop is accelerated during the germination and flowering phases, and slightly decreases at the end of the growing season. It has been established that the optimal rate of fertilizer application will reduce the transpiration rate of the bark plant and produce a high yield of water. Yields of bark varieties are mineral fertilizersN120-150P90K60Increase to the kg / ha variability has been observed, and excess of this norm does not have a positive effect on productivity. Mineral fertilizers of the Kazan variety of lentils grown as a secondary cropN120P90K60The most effective yield (21.7 centner / ha) was obtained in the usual kg / ha. The highest yield (23.1 t / ha) in the larch “Krupinka” is a mineral fertilizer N150P90K60kg / ha.